EFFECTS OF THE ADDITION OF CANTHARELLUS CIBARIUS MUSHROOMS ON THE RHEOLOGICAL PROPERTIES OF BUTTERMILK - OVIDIU TIȚA; OANA-MARIA POPA; MIHAELA-ADRIANA TIȚA; MARIA ADELINA CONSTANTINESCU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The purpose of the work is to obtain buttermilk with the addition of mushrooms and to evaluate some quality characteristics of the final product. Edible mushrooms such as Cantharellus cibarius have a multitude of health benefits. They contain a series of nutrients, ensure efficient digestion, they are very good for increasing immunity. In the proposed research, the evolution of a buttermilk product was followed by the enrichment with mushrooms in different amounts of 10, 15 and 20 grams compared to the normal product. As a section of mushrooms, the attention was focused on the species Cantharellus cibarius often found in Romania. The assortments developed in different concentrations were compared from a physico-chemical point of view in order to note all the aspects that the mushroom species brings to buttermilk product. In order to obtain the products, we started from the technology of obtaining buttermilk products with usual additions, and after the seeding process, before the product was packaged, the mushrooms were added in powder form, in the established concentrations. From the analysis of the obtained results, it appears that the samples showed a decrease in acidity during the analyzed period, due to the appearance of the syneresis phenomenon, the product becoming more fluid. Viscosity analysis shows that the sample with the addition of 20 grams of mushrooms had the highest weight compared to the control sample with the lowest value.